Efektivitas Model Pembelajaran Discovery Learning dan Model Pembelajaran Inquiry Learning terhadap Hasil Belajar Tematik Kelas IV Sekolah Dasar - Agus Robiyanto; Suhandi Astuti (FONDATIA, 2022)
This study aims to determine the effectiveness of the learning model of Discovery Learning and Inquiry Learning on thematic learning outcomes of fourth grade elementary school students. This research is a quasi-experimental research using a research design that is Noneguivalent Control Group Design. The population in this study were fourth grade elementary school students in the Merbabu cluster. Determination of the sample by using a non-probability sampling technique purposive sampling type. The research sample used was the fourth grade students of SD Negeri Kopeng 03 with a total of 21 people, class IV students of SD Negeri Batur 03 with a total of 21 people, and class IV students of SD Negeri Batur 01 with a total of 17 people. So the total number of samples used in the study were 59 students. The method used is observation and test. All elementary schools used as research were experimental group 1 and experimental group 2 by dividing into two groups. The treatment using the Discovery Learning learning model was used in the experimental group 1 while the Inquiry Learning learning model was used in the experimental group 2. Based on the research results, the average value of the learning outcomes for the experimental class 1 was 72.18 and in the experimental class 2 was 64.25. The results of the t-test obtained that the t-count value is 2.837 with sig. (2-tailed) 0.006 and sig. (1 – tailed) 0.003 and df of 57. Probability value <0.05 then Ho is rejected and Ha is accepted. It can be concluded that the application of the Discovery Learning model is significantly more effective than the Inquiry Learning model on thematic learning outcomes for fourth grade elementary school students.